PHYSICAL THERAPY FOR CHILDREN WITH MUSCULAR TORTICOLLIS (Physical Culture and Sport: Scientific Perspective, 2025)
Torticollis in early childhood is one of the most common muscular disorders requiring immediate intervention, as timely correction of this issue prevents skull deformities, restricted cervical spine movement, motor skill development disorders, and postural asymmetry. The prevalence of torticollis among musculoskeletal disorders ranges from 5% to 12%, ranking third after hip dysplasia and clubfoot. Conservative treatment of torticollis in early childhood includes a series of measures aimed at optimizing muscle tone, resolving hematomas in the sternocleidomastoid muscle, normalizing the position of the child’s head, and eliminating existing signs of asymmetry. An analysis of modern randomized studies, particularly international ones, indicates that physical therapy is the primary method of treating torticollis in newborns and young children. Several studies have evaluated the effectiveness of passive and active neck muscle stretching methods, which resulted in significant improvements in mobility and alignment of the head position. The leading methods of physical therapy in early childhood include passive muscle stretching, active muscle stretching, development of active symmetrical movements, adaptation of the environment, and teaching parents or caregivers positioning skills and the nuances of childcare in daily family life. An individualized approach and high-quality selection of physical therapy techniques are key to achieving positive outcomes, minimizing the risk of adverse disease consequences, and reducing the duration of treatment. Regular assessment of therapy progress is essential to adjust treatment approaches in line with the individual needs of the patient. The success of therapy depends on the timely initiation of treatment, the competent selection of therapeutic methods, and the active involvement of parents in the rehabilitation process.
Keywords: torticollis; treatment; physical therapy; early delivery; children